THE SITUATION IN THE LATGALIAN COUNTRYSIDE AT THE BEGINNING OF THE AGRARIAN REFORM IN THE 1920s - Malahovskis, Vladislavs (Via Latgalica, 2008)
During the first independence of the Latvian Republic, the radical agrarian reform between 1920 and 1937 was the most important attempt to solve the agrarian problem. At the core of the reform was the nationalization of the estates, the buildings, the interior inventory and the cattle, and the distribution of the land which had become property of the National Land Fund (NLF) among landless peasants and small farmers. The objective of the paper is to identify the different factors that cumbered the beginning of the agrarian reform in Latgale and made it more complicated. In Latgale there was a big problem to abandon the system of land management under collective responsibility, which slowed down the personal initiative of the farmers and therefore constrained the introduction of more progressive methods of land cultivation and management. In Latgale, as a long-term adminstrative part of the guberniya of Vitebsk, archaic methods of managementi similar to those in Russia prevailed. After the formation of the Latvian state, when the region of Latgale joined the better developed regions of Vidzeme, Kurzeme and Zemgale, the agrarian underdevelopment of Latgale became particularly obvious. Therefore, eliminating this gap in the agrarian development became one of the most important tasks on the way to an economically and politically stable state. Although the Latvian law on the Agrarian reform was meant to apply to the whole territory of Latvia, the agrarian reform in Latgale needed to react to peculiarities that demanded additional measures. While preparing and implementing the agrarian reform in Latgale, it was necessary to consider the historical „heritage” from the times when Latgale was part of the Polish- Lithuanian state and the Russian Empire: - A non-efficient system of management which was based on rural management expertise; - An artificially created shortage of land among the Latgalian, i.e. Catholic farmers, since there were restrictions for them in land purchasing; - Poorly educated and conservative farmers. Since 1917, the situation of the Latgalian farmers became worse because of unlawful activities by different armies such as the requisition of cattle and looting. Because of the continuing existence of the Soviet regime until January, 1920, the registration of landless peasants and the land assignment started later in Latgale than in other regions. When the land assignment in Latgale started, at first the data that the land surveyors and regional managers of the National Land Fund had gathered on site had to be processed. The precise area under the administration of the National Land Fund was not known, nor was the area of the land which was used for agricultural purposes. There were no maps of the major part of the estate and village lands in Latgale. As long as Latgale used to be the part of the Guberniya of Vitebsk, there was no data about Latgale. Many archives of the agrarian commission were destroyed by the communists in 1919, and during World War I parts of them had already been taken to Russia. There was no organized land register in Latgale. From a legal point of view, the land was registered under the name of one owner, but in reality many heirs often cultivated the land together. In addition, there were some legally registered shared land properties in Latgale. There were not many landless peasants in Latgale, but there were indeed many small farmers who had obtained the right to acquire additional land. The quantity of the land of the National Fund in Latgale did not correspond to the large number of land claims. In Latgale, about 60% of the small farmers had a right to claim land. Since the procedure of land assignment was therefore much more difficult in Latgale than in other Latvian regions, the special instruction № 25 was drafted for Latgale in addition to the law on the agrarian reform. This instruction regulated the principles of land assignment from the National Fund in the region. The instruction provided for greater privileges for land claims put forward by locals. Although there were a lot of difficulties and problems during the preparation of the agrarian reform and the land assignment in Latgale, it finally proved to be a great achievement for the solution of the agrarian problems in Latvia in general.